Penggunaan Bahasa Persuasif dalam Buku Pengayaan Digital Literasi: Pendekatan Retorika terhadap Tema Eco Green - Sumirah Sumirah; Ida Zulaeha; Hari Bakti Mardikantoro; Haryadi Haryadi (Balai Bahasa Provinsi Bali, 2025)
This study analyzes the use of persuasive language in eco-green literacy digital enrichment books for junior high school students through a rhetorical approach. By combining critical discourse analysis (CDA) and classical rhetorical theory (pathos, logos, ethos), this study identifies effective linguistic strategies in conveying environmental messages. The research method uses a descriptive qualitative approach with a case study design. Data collection techniques include: (1) document analysis of 15 eco green digital books for junior high schools, (2) in-depth interviews with 12 students and 8 teachers, (3) participatory observation during the implementation of teaching materials for 3 months, and (4) focus group discussions (FGD) with linguistics and environmental education experts. Data analysis was carried out through triangulation of methods using the Miles & Huberman model (data reduction, data display, verification) combined with Aristotle's rhetorical analysis framework and thematic coding techniques to identify linguistic persuasive patterns. The results of the study show that the combination of emotional narrative (pathos), scientific facts (logos), and source credibility (ethos) successfully builds students' ecological awareness, improves conceptual understanding, and encourages real action. Concrete examples such as the story